Work-family conflict and family-work conflict on worker’s work roles effectiveness in the call centre industry in Klang valley: a comprehensive model / Raslan Nordin ...[et al.] - Nordin, Raslan; Ghazali, Norfazlina; Mohamad Mozie, Noorizan; Che Din, Suryani (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, 2018)
Call Centre industry has been the most challenging and yet highly stressful environment work place. Call Centre are known implementing high target as well as rotating shift pattern that further challenges by causing conflicts on the employee’s focus between work and family. This study will focus on work-family conflict challenges and solutions among employees and organizations in the Malaysia on the Asian context. Is it imperative to find the relationship between work and family with the employee’s Job Role, Career Role, Innovation Role, Team Role, and Organization Role. The research will adopt the quantitative approach using the survey (through a structured questionnaire). Primary data for this research will be collected from original sources through distribution of questionnaires to employees of call centre organizations in Klang Valley. The findings are expected to benefits the employee’s, the human resource professional and the organization itself.